Analisis Minat Konsumen Terhadap Produk Cicilan Emas: Studi Kasus Bank Muamalat KCP Lamongan - Rika Nur Amelia; Ananta Delyana Mafikah; Silvi Indah Nurvita Sari (Al-Musthofa: Journal of Sharia Economics, 2025)
This study aims to analyze consumer interest in gold installment products at Bank Muamalat KCP Lamongan. This product is one of the sharia financing services that provides convenience to the public in owning gold gradually. Consumer interest is an important initial indicator in determining the potential success of a product, especially in the context of sharia finance. This study uses a qualitative descriptive approach with data collection techniques through literature studies, observations and interviews with customers and banks directly involved in gold installment services.The results of the study indicate that consumer interest is quite high, which is influenced by factors of ease of service, sharia principles used, and bank marketing strategies. However, there are still obstacles such as the unavailability of gold financing in cash and the lack of public literacy in gold installment financing which results in a lack of information received. This study suggests the need to increase education and product promotion in order to reach and be able to fulfill the needs of the community.